A retrospective study for the diagnostic value of chromosomal microarray analysis in fetuses with high-risk prenatal indications - Xiao, Hui; Xiao, Junfang; Zhang, Huan; Huang, Shuhui; Lu, Qing; Yuan, Huizhen; Zou, Yongyi; Yang, Bicheng; Liu, Yanqiu (Frontiers in Genetics, 2025)
ObjectiveThe aim of this study was to determine the diagnostic value of prenatal chromosomal microarray analysis (CMA) for fetuses at high risk for various conditions on chromosomal abnormalities.MethodsIn the study, 8,560 clinical samples were collected from pregnant women between February 2018 and June 2022, including 75 villus, 7,642 amniotic fluid, and 843 umbilical cord blood samples. All samples were screening for chromosomal abnormalities using both CMA and karyotyping. This retrospective analysis included 8,560 pregnancies with high-risk indications for invasive prenatal diagnosis, mainly including ultrasound anomalies, high risk for maternal serum screening (MMS), high risk for non-invasive prenatal tests (NIPTs), family history of genetic disorders or birth defects, and advanced maternal age (AMA). All samples were evaluated using invasive CMA. The rate of clinically significant genomic imbalances between the different groups was compared.ResultsThe success rate of CMA was 99.95% (8,556/8,560). A total of 1,037 samples (12.11%, 1,037/8,560) were presented with chromosomal abnormalities using CMA, whereas 803 samples (9.38%, 803/8,560) were shown with chromosomal abnormalities using karyotyping. The overall prenatal diagnostic yield was 1,040 (12.14%) of 8,560 pregnancies. Clinically significant genomic aberrations were identified in 153 (6.21%) of 2,463 patients with non-structural ultrasound anomalies, 79 (6.38%) of 1,238 with structural ultrasound anomalies, 37 (4.26%) of 868 at high risk from MSS, 395 (42.29%) of 934 at high risk from NIPTs, 16 (2.94%) of 544 with a family history, 7 (1.89%) of 369 with AMA, 1 (1.56%) of 64 with a history of adverse exposure, 10 (4.46%) of 224 with parental chromosome anomaly, and 9 (2.99%) of 301 with other indications.ConclusionCMA has a greater diagnostic value for screening chromosomal abnormalities, especially in pregnant women with normal karyotypes. The diagnostic yields of CMA for pregnancies with different indications greatly varied. CMA could serve as a first-tier test for structural anomalies, especially multiple anomalies, hydrops fetalis, cystic hygroma, and thickened nuchal translucency or nuchal fold.